2015
DOI: 10.1002/tre.446
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of non-muscle-invasive bladder cancer

Abstract: Although there has been an overall reduction in the incidence of bladder cancer, the mortality rate has remained unchanged, hence survival is now worse. Most patients have non‐muscle‐invasive bladder cancer at presentation, which is not immediately life threatening, so efforts must be made to improve the early diagnosis and expeditious treatment of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Retrospective analysis of most hospital-based studies in developing countries have shown that gross hematuria is the commonest presenting symptoms followed by irritative symptoms associated with UTI (Table 2, [7, 8, 12, 13, 15, 16-23]). A prospective study by (Edward et al) in UK involving 4,020 patients with hematuria showed macroscopic hematuria was associated with an 18.9% risk of urinary tract malignancy, while non-visible or microscopic hematuria was associated with a 4.8% risk of malignancy [9, 27].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Retrospective analysis of most hospital-based studies in developing countries have shown that gross hematuria is the commonest presenting symptoms followed by irritative symptoms associated with UTI (Table 2, [7, 8, 12, 13, 15, 16-23]). A prospective study by (Edward et al) in UK involving 4,020 patients with hematuria showed macroscopic hematuria was associated with an 18.9% risk of urinary tract malignancy, while non-visible or microscopic hematuria was associated with a 4.8% risk of malignancy [9, 27].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of bladder cancer ultimately depends on cystoscopic examination of the bladder [1, 3, 9, 10] and histological evaluation of the resected tissue [2] although about 4% of cases will be found incidentally, usually during imaging to investigate non-urological symptoms [9]. However, the detection rate for white light cystoscopy (WLC) can be limited (as low as 60%) [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations